Risks and Benefits of Magnesium Sulfate Tocolysis in Preterm Labor (PTL) - John C. Morrison; James A. Bofill; John P. Elliott (AIMS Press, 2016)
The U.S. Food and Drug Administration issued a drug safety communication on 05/30/2013 recommending "against prolonged use of magnesium sulfate to stop preterm labor (PTL) due to bone changes in exposed babies." In September of 2013, The American Congress of Obstetrics and Gynecologists issued Committee Opinion No. 573 " Magnesium Sulfate Use in Obstetrics" , which supports the short term use of MgSO4 to prolong pregnancy (up to 48 hrs.) to allow for the administration of antenatal corticosteroids." Are these pronouncements by respected organizations short sighted and will potentially result in more harm than good? The FDA safety communication focuses on bone demineralization (a few cases with fractures) with prolonged administration of MgSO4 (beyond 5-7 days). It cites 18 case reports in the Adverse Event Reporting System with an average duration of magnesium exposure of 9.6 weeks (range 8-12 wks). Other epidemiologic studies showed transient changes in bone density which resolved in the short duration of follow up. Interestingly, the report fails to acknowledge the fact that these 18 fetuses were in danger of PTD and the pregnancy was prolonged by 9.6 weeks (e.g. extending 25 weeks to 34.6 wks), thus significantly reducing mortality and morbidity. Evidence does support the efficacy of MgSO4 as a tocolytic medication. The decision to use magnesium, the dosage to administer, the duration of use, and alternative therapies are physician judgments. These decisions should be made based on a reasonable assessment of the risks of the clinical situation (PTL) and the treatments available versus the benefits of significantly prolonging pregnancy.